The impact of decreased environmental reward in predicting depression severity in caregivers - Vázquez González, Fernando Lino; López, Lara; Blanco, Vanessa; Otero, Patricia; Torres, Ángela J.; Ferraces, María José (Anales de Psicología / Annals of Psychology, 2019)
Reward has not been examined as a predictor of depression in the caregiver population despite the high prevalence of depression. The aim of this study was to analyze reward as a predictor of the level of depression (without depression, subclinical depression, major depressive episode) in caregivers. Independent evaluators evaluated the socio-demographic variables of the caregiver, the person receiving care, the situation of care, reward and depressive symptomatology through self-reports. Expert clinicians evaluated the prevalence of major depressive episodes using the SCID-5-CV in 592 caregivers (87.2% women, average age = 55.4 years). The average reward score was 28.1. Reward was lower in caregivers younger than 55 years old who belonged to a low/low-middle social class. Reward was higher in caregivers without depression than in those with subclinical depression and a major depressive episode. Reward was also higher in caregivers with subclinical depression versus those with a major depressive episode. Caregivers with higher reward had a lower probability of subclinical depression (adjusted OR = 0.78, 95% CI 0.75-0.83) and a major depressive episode (adjusted OR = 0.67, 95% CI 0.62-0.72). Reward was a protective factor against subclinical depression and a major depressive episode in caregivers.